Sistemas inteligentes de colheita de energia vibracional induzida por escoamento interno - Caetano, Pedro Cardoso (2020)
Smart materials have been explored in recent years as a solution in many applications that require efficient and small devices. Based on these materials, the use of vibrational energy for power generation through energy harvesting devices is studied in this paper. The vibrational energy comes from the lateral vibration of ducts with internal flow. A device based on smart material, piezoelectric or magnetostrictive, is excited by this mechanical vibration source, where the objective is the generation of output power through a coupled electrical circuit, as well as the comparison between smart materials. In addition to this comparison, a scale reduction study is carried out comparing the energy density generated with the miniaturization of the energy harvesting system. Improvements to the device are discussed with the aim of operating over a wider frequency range. In this sense, a magnetic interaction with magnets is introduced, generating a nonlinear behavior of the magnetic force. The results show that the magnetostrictive material Galfenol has a better performance when compared to piezoelectric material. Regarding the configuration with the presence of magnets, a rich dynamic is observed, with periodic and non-periodic responses. By comparison with the linear system, there is an increase in the power generated and an increase in the frequency range.